Method for producing porous body and porous body
The production of a highly strong and thermally resistant porous body using a liquid crystal polymer powder with fine fibrous particles addresses the limitations of existing methods, achieving enhanced strength and filtration properties.
Patent Information
- Application Number
- JP2023556597
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-29
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-10-26
AI Technical Summary
Existing methods for producing porous bodies using liquid crystal polymer (LCP) face challenges such as limited high-temperature usability, weak strength, and the need for narrow temperature control during melt blowing, as well as limitations in achieving dense porous structures and fine pore sizes.
A porous body is created using a liquid crystal polymer powder with fibrous particles of 2 μm or less in diameter, achieving an average pore diameter of less than 10 μm and a tensile strength of 25 N/mm², without the use of adhesives, which enhances heat resistance and reduces water absorption.
The resulting porous body exhibits high strength and improved thermal and moisture resistance, while maintaining a fine pore structure suitable for filtration and other applications.
Smart Images

Figure 0007666629000002 
Figure 0007666629000003 
Figure 0007666629000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous body and a method for producing a porous body. [Background technology]
[0002] Generally, polymeric porous bodies are classified into fiber-based nonwoven fabrics and porous films based on film manufacturing methods (Patent Documents 1 to 7). In addition, when forming a polymeric porous body using a liquid crystal polymer (LCP), even if a nonwoven fabric is formed from fibers obtained by a general melt spinning method, only a porous body with a coarse fiber diameter and large pores can be obtained, so in order to obtain a porous body with fine pores, it is necessary to use an LCP with fine fibers.
[0003] Methods for forming nonwoven fabrics using fine fiber LCP include, for example, papermaking and melt-blowing, while methods for forming porous films include, for example, stretching a filler-containing LCP film and phase separation. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-129392 A [Patent Document 2] JP 2000-119952 A [Patent Document 3] JP 2003-26866 A [Patent Document 4] JP 2005-120535 A [Patent Document 5] JP 2002-61063 A [Patent Document 6] JP 2017-514315 A [Patent Document 7] JP 2012-224692 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when a nonwoven fabric is formed by a papermaking method, there are problems such as inability to be used at high temperatures, the porous body being crushed, low strength, etc. Furthermore, when a nonwoven fabric is formed by a melt-blowing method, there are problems such as the need to form the fabric within a narrow temperature range because the melt viscosity is highly temperature dependent and the fluidity changes even with a slight increase or decrease in temperature.
[0006] When a porous film is formed by stretching a filler-containing LCP film, the film only has small through-holes, and does not have a dense pore structure. In addition, when a porous film is formed by the phase separation method, only LCP that dissolves in a solvent can be used.
[0007] In view of the above problems, an object of the present disclosure is to provide a porous body having high strength by using an LCP having fine fibers. [Means for solving the problem]
[0008] The porous body of the present disclosure is A porous body containing a liquid crystal polymer powder, The liquid crystal polymer powder contains fibrous particles made of a liquid crystal polymer, The average diameter of the fibrous particles made of the liquid crystal polymer is 2 μm or less, The average pore size measured by mercury intrusion porosimetry is 10 μm or less. 25N / mm 2 It has a tensile strength of at least 100%. Effect of the Invention
[0009] According to the present disclosure, a porous body with high strength can be provided by using an LCP having fine fibers. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the heating temperature in the heating step and the tensile strength for Examples 1 to 3 and Comparative Example 1. [Diagram 2] FIG. 2 is a graph showing the relationship between the heating temperature in the heating step and the tensile strength for Examples 4 to 6 and Comparative Example 2. [Diagram 3] FIG. 3 is a photograph of a cross section of the porous body in Example 1. [Figure 4] FIG. 4 is a photograph of a cross section of the porous body in Example 2. [Diagram 5] FIG. 5 is a photograph of a cross section of the porous body in Example 3. [Figure 6] FIG. 6 is a photograph of a cross section of the porous body in Comparative Example 1. [Figure 7] FIG. 7 is a photograph showing a cross section of the porous body in Reference Example 1. As shown in FIG. [Figure 8] FIG. 8 is a photograph of a cross section of the porous body in Example 7. [Figure 9] FIG. 9 is a flow diagram showing the steps of producing the porous body according to the first embodiment. [Figure 10] FIG. 10 is a flow diagram showing the steps of producing the porous body according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described, but the present disclosure is not limited to these.
[0012] [First embodiment] <Porous body> The porous body according to the present embodiment contains liquid crystal polymer powder (LCP powder), and the liquid crystal polymer powder contains fibrous particles (liquid crystal polymer fibers: LCP fibers) made of liquid crystal polymer, and the average diameter of the LCP fibers is 2 μm or less. The porous body has an average pore diameter of 10 μm or less as measured by mercury intrusion porosimetry, and has a pore size of 25 N / mm 2 It has a tensile strength of at least 100%.
[0013] (Liquid Crystal Polymer Powder) The liquid crystal polymer is not particularly limited, but examples thereof include thermotropic liquid crystal polymers, etc. Thermotropic liquid crystal polymers are aromatic polyesters synthesized mainly from monomers such as aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids, and exhibit liquid crystallinity when melted.
[0014] The molecules of liquid crystal polymers have a negative coefficient of linear expansion (CTE) in the axial direction of the molecular axis and a positive CTE in the radial direction of the molecular axis.
[0015] The liquid crystal polymer is preferably free of amide bonds. Examples of thermotropic liquid crystal polymers free of amide bonds include copolymers of parahydroxybenzoic acid, terephthalic acid and dihydroxybiphenyl (copolymers of parahydroxybenzoic acid and ethylene terephthalate) which have a high melting point and low CTE and are called type 1 liquid crystal polymers, and copolymers of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid which have a melting point between type 1 liquid crystal polymers and type 2 liquid crystal polymers, called type 1.5 (or type 3).
[0016] The LCP fibers contained in the LCP powder are not particularly limited as long as they contain a fibrous portion, which may be linear or may have branches.
[0017] The average diameter of the LCP fibers is 2 μm or less, and preferably 1 μm or less, and the average aspect ratio of the LCP fibers is preferably 10 or more and 500 or less, and more preferably 10 or more and 300 or less.
[0018] The average diameter and average aspect ratio of the LCP fibers are measured by the following method.
[0019] LCP powder made of LCP fibers to be measured is dispersed in ethanol to prepare a slurry in which 0.01% by mass of LCP powder is dispersed. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is arranged on the slide glass. Next, a predetermined area of the LCP powder placed on the slide glass is observed with a scanning electron microscope (SEM) to collect 100 or more image data of the particles (LCP fibers) constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In addition, in order to prevent the occurrence of missed image data collection or measurement errors for each LCP particle, the magnification of the SEM is appropriately changed to 500x, 3000x, or 10000x to collect the image data. Next, using the collected image data, the longitudinal dimension and width dimension of each of the LCP fibers are measured. For one LCP fiber captured in each of the image data, the direction of the straight line connecting both ends of the longest path from one end of the fiber through approximately the center of the particle to the opposite end of the fiber is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension. In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder, and the average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder. Furthermore, the ratio of the longitudinal dimension to the fiber diameter [longitudinal dimension / fiber diameter] is calculated to obtain the aspect ratio of the LCP fiber. The average value of the fiber diameters measured for 100 LCP fibers is taken as the average diameter. The average aspect ratio is determined as the average value of the aspect ratios measured for 100 LCP fibers.
[0020] The fibrous particles may be contained in the LCP powder as aggregates of the fibrous particles.
[0021] In addition, the axial direction of the LCP molecules constituting the fibrous particles tends to coincide with the longitudinal direction of the fibrous particles. This is believed to be because, when an LCP powder is produced, destruction occurs between a plurality of domains formed by bundling the LCP molecules, causing the axial direction of the LCP molecules to be oriented along the longitudinal direction of the fibrous particles.
[0022] In the LCP powder, the content (number ratio) of particles other than fibrous particles (aggregated particles that are not substantially fibrous) is preferably 20% or less. For example, when the LCP powder is placed on a flat surface, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are aggregate particles.
[0023] The LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.
[0024] (Average pore diameter) The porous body of the present embodiment has an average pore diameter of 10 μm or less. Here, the "average pore diameter" refers to a pore diameter at which the cumulative pore distribution of the pore distribution measured by mercury intrusion porosimetry is 50% of the total pore volume. If the average pore diameter of the porous body exceeds 10 μm, the functions of the porous body, such as filtration performance, may not be sufficiently obtained. The average pore diameter of the porous body is preferably 5.0 μm or less. In addition, the average pore diameter of the porous body may be 0.1 μm or more, or may be 0.3 μm or more.
[0025] (Tensile strength) The porous body of this embodiment has a resistance of 25 N / mm 2In the present embodiment, the tensile strength is the value (N / mm) obtained by dividing the load at which a test piece of 5 mm × 25 mm taken from a porous body is broken when the test piece is stretched under conditions of a gripping distance of 13 mm and a tensile speed of 0.6 mm / min, by the cross-sectional area excluding the pores. 2 By specifying it in this way, it is possible to compare the tensile strength of porous bodies with different film thicknesses without being affected by the film thickness. The tensile strength of the porous body is 40N / mm 2 It is preferable that the resistance is 60N / mm or more. 2 More preferably, it is equal to or greater than this.
[0026] (Additives) The porous body of the present embodiment may contain an additive. When the porous body contains an additive, the function of the additive, for example, water repellency, oil repellency, heat dissipation, etc., can be imparted to the porous body. Examples of the additive include inorganic filler, polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), carbon fine powder, carbon fine fiber, metal powder, nitride powder, etc. Examples of the nitride powder include boron nitride powder, aluminum nitride powder, silicon nitride powder, etc.
[0027] In addition, the porous body of the present embodiment does not contain an adhesive for bonding the LCP fibers together. This is because the porous body of the present embodiment achieves the above-mentioned tensile strength by bonding the LCP fibers together by heating. In addition, the inclusion of an adhesive may cause problems such as a decrease in heat resistance and an increase in water absorption.
[0028] <Method of manufacturing porous body> Each step of the manufacturing method according to this embodiment will now be described.
[0029] As shown in FIG. 9, the method for producing a porous body according to this embodiment includes a dispersing step (S1), a matte-forming step (S2), and a heating step (S3).
[0030] First, the method for producing the LCP powder used in the dispersion step (S1) will be described in detail. The LCP powder can be produced, for example, by carrying out the following coarse pulverization step, fine pulverization step, coarse particle removal step, and fiberization step in this order.
[0031] The shape of the raw material (LCP raw material) made of LCP used to prepare the LCP powder can be, for example, uniaxially oriented pellets, biaxially oriented film, powdered LCP, etc. The LCP constituting the LCP raw material is the same as the LCP constituting the above-mentioned LCP fiber.
[0032] (Coarse grinding process) In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as it can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.
[0033] It is not always necessary to carry out the coarse pulverization step. For example, if the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material may be used directly as a raw material for the fine pulverization step.
[0034] (Fine grinding process) In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized while being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).
[0035] In the pulverization step, it is preferable to use media to pulverize the LCP raw material dispersed in liquid nitrogen. The media is, for example, beads. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by IMEX.
[0036] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.
[0037] (Coarse particle removal process) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved with a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular LCP that remains above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and an example of the mesh is one with an opening of 53 μm. The coarse particle removal step is not necessarily required.
[0038] (Fiberization process) Next, in the fiberization process, the granular LCP is crushed by a wet high-pressure crushing device to obtain LCP powder. In the fiberization process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The finely pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or mixtures thereof.
[0039] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through the nozzle under high pressure. By passing through the nozzle under high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the LCP, crushing the granular finely pulverized LCP, and the fiberization of the LCP progresses, and an LCP powder consisting of fine LCP fibers can be obtained. From the viewpoint of applying high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which the finely pulverized LCP does not clog the nozzle. Since the particle diameter of the granular finely pulverized LCP is relatively small, the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.
[0040] As described above, a plurality of fine cracks are formed in the granular pulverized LCP. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The expansion of the dispersion medium that penetrates into the inside of the pulverized LCP causes destruction to proceed from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the LCP molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the fine pulverization process in this embodiment, an LCP powder having a lower content of aggregated particles and consisting of fine LCP fibers can be obtained, compared to the LCP powder obtained by crushing the granular LCP obtained by the conventional freeze-pulverization method.
[0041] In the fiberization process of the present embodiment, the finely pulverized LCP may be crushed multiple times using a wet high-pressure crushing device to obtain LCP powder. However, from the viewpoint of production efficiency, it is preferable to crush the LCP using the wet high-pressure crushing device a small number of times, for example, 5 times or less.
[0042] (Dispersion process: S1) In the dispersion step, which is the first step in the method for producing a porous body, the above-mentioned LCP powder is dispersed in a dispersion medium to form a paste or slurry. In this manner, in the present embodiment, the above-mentioned fine fibrous LCP powder is used, so that the LCP powder can be dispersed in a dispersion medium with high viscosity.
[0043] Examples of the dispersion medium used in the dispersion step include butanediol, water, ethanol, terpineol, a mixture of water and ethanol, etc. For example, when butanediol is used as the dispersion medium, a paste-like LCP powder is obtained. When a mixture of water and ethanol is used as the dispersion medium, a slurry-like LCP powder is obtained.
[0044] Furthermore, when manufacturing a porous body containing an additive, the LCP powder and the additive are mixed in this step to obtain a paste-like or slurry-like mixture of the LCP powder and the additive (hereinafter, the mixture of the LCP powder and the additive may be simply referred to as a "mixture"). The mixing ratio of the additive is preferably 50 volume % or less of the mixture.
[0045] (Matting process: S2) Next, in the mat-forming step, the paste or slurry LCP powder or mixture is dried to form a liquid crystal polymer fiber mat (LCP fiber mat). In this embodiment, the mat-forming step is, for example, a papermaking method. In the papermaking method, the dispersion medium used in the dispersion step can be easily recovered and reused, and the porous body can be produced at low cost.
[0046] Specifically, in the mat-making process using the papermaking method, a slurry-like LCP powder or mixture is first papered onto a mesh, a nonwoven microporous sheet, or a woven fabric, and then the slurry-like LCP powder or mixture placed on the mesh is heated and dried to obtain an LCP fiber mat.
[0047] In the mat-forming step of the present embodiment, instead of the above papermaking method, a paste-like LCP powder or mixture may be formed into an LCP fiber mat by a coating step and a drying step.
[0048] In the coating step, the paste-like LCP powder or mixture is coated on a substrate. Here, the term "substrate" refers to a material or support for coating the paste-like LCP powder or mixture, and examples of such materials include metal foils such as copper foil, polyimide films, PTFE films, and composite sheets made of reinforcing materials such as carbon fibers or glass fibers and heat-resistant resins.
[0049] Next, in a drying step, the paste-like LCP powder or mixture applied to the substrate is heated and dried to evaporate the dispersion medium, forming an LCP fiber mat on the substrate.
[0050] In addition, in the drying process, the dispersion medium is gradually removed from the paste-like LCP powder or mixture, so that the overall thickness of the paste-like LCP powder or mixture gradually decreases during drying, and therefore the thickness of the LCP fiber mat becomes thinner than the overall thickness of the paste-like LCP powder or mixture formed on the product.
[0051] Furthermore, as the overall thickness of the paste-like LCP powder or mixture gradually decreases during drying, the longitudinal direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, those having a longitudinal direction in the overall thickness direction of the paste-like LCP powder or mixture tilt so that their longitudinal direction faces the main in-plane direction of the substrate. Therefore, the longitudinal direction of the fibrous particles in the formed LCP fiber mat is anisotropic.
[0052] In the matting step, a paste-like LCP powder or mixture may be applied on the LCP fiber mat formed on the substrate by the drying step, and then the mixture may be dried to evaporate the dispersion medium. In this manner, the matting step may include a coating step and a drying step repeated in this order. This allows an LCP fiber mat having a desired basis weight to be obtained. In addition, when the coating step and the drying step are repeatedly performed, a mixture in which the mixing ratio of the LCP powder and the additive is changed for each coating step may be used. This allows an LCP fiber mat capable of forming a porous body having desired properties to be obtained.
[0053] (Heating process: S3) Next, in the heating step, the LCP fiber mat is heated to obtain a porous body. In addition, the heating step may be performed under an inert gas atmosphere. In this way, the tensile strength of the porous body can be further improved.
[0054] The heating temperature in the heating step is in the range of -60°C to -5°C of the melting point of the LCP powder. If the heating temperature is lower than -60°C of the melting point of the LCP powder, the adhesion between the LCP fibers is weak, and a porous body having practical strength cannot be obtained. If the heating temperature is higher than -5°C of the melting point of the LCP powder, the LCP fibers soften and deform, making it impossible to maintain the porous structure. The heating temperature is preferably in the range of -50°C to -10°C of the melting point of the LCP powder, and more preferably in the range of -40°C to -20°C of the melting point of the LCP powder.
[0055] The holding time in the heating step is not particularly limited and may be, for example, 5 minutes or more, or may be 15 minutes or more. In addition, since a porous body with higher strength is obtained by holding for a long period of time, the holding time may be, for example, 30 minutes or more, or may be 60 minutes or more.
[0056] In the matting process, when an LCP fiber mat is formed on the substrate by the coating process and drying process, the LCP fiber mat is heated together with the substrate. This makes it possible to obtain a porous body with the substrate bonded thereto at low cost. In addition, a paste-like LCP powder or mixture can be applied to a necessary portion of the substrate and dried to form a porous body partially on the substrate or a three-dimensional porous body.
[0057] [Embodiment 2] <Porous body> The porous body of this embodiment differs from that of embodiment 1 in that it has an average pore diameter of 1.0 μm or less. It is considered that a porous body with a fine average pore diameter is excellent in strength, filtration characteristics, etc. Other points are the same as those of embodiment 1, and therefore repeated explanations will be omitted.
[0058] <Method of manufacturing porous body> As shown in Fig. 10, the method for producing a porous body according to the present embodiment includes a dispersion step (S10), a matte-forming step (S20), a hot pressing step (S30), and a heating step (S40). Each step of the production method according to the present embodiment will be described below. Note that descriptions that overlap with those of the first embodiment will be omitted.
[0059] (Dispersion process: S10) In the dispersion process, the LCP powder and the binder resin are dispersed in a dispersion medium to form a paste or slurry-like resin mixture. By mixing the binder resin in the dispersion process and forming it into a film in the heat press process described below, it is expected that the handling properties will be improved, such as making it easier to process before producing a porous body.
[0060] Examples of the binder resin used in the dispersion step include acrylic resin, butyral resin, and ethyl cellulose resin. Among these, acrylic resin is preferred from the viewpoint of decomposability. The mixing ratio of the binder resin is preferably 30% by volume or more and 70% by volume or less with respect to the resin mixture. In addition, the average diameter of the binder resin is preferably 10 μm or less.
[0061] When a porous body containing an additive is produced, the LCP powder, binder resin, and additive are mixed in this step.
[0062] (Matting process: S20) Next, in the matting step, the paste or slurry-like resin mixture or the resin mixture containing additives is dried to form a resin mixture mat.
[0063] (Hot pressing process: S30) Next, in the hot pressing step, the resin mixture mat is hot pressed to obtain a resin mixture film.
[0064] The heating temperature in the hot pressing step is 20°C or higher and 100°C or lower. If the heating temperature is lower than 20°C, the binder resin does not soften and it is difficult to form a film. If the heating temperature exceeds 100°C, the binder resin flows. The heating temperature is preferably 40°C or higher and 80°C or lower.
[0065] The pressure in the heat pressing step is 0.3 MPa or more and 3.0 MPa or less. If the pressure is less than 0.3 MPa, the pressure is insufficient and air bubbles remain. If the pressure exceeds 3.0 MPa, the binder resin flows. The pressure is preferably 0.5 MPa or more and 1.0 MPa or less.
[0066] The holding time in the hot pressing step is not particularly limited, and may be, for example, 1 minute or more, or 10 minutes or more.
[0067] (Heating process: S40) Next, in the heating step, at least a part of the binder resin contained in the resin mixture film is heated and removed to obtain a porous body. The porous body may contain a binder resin. The proportion of the remaining binder resin is adjusted by the heating temperature and the holding time in the heating step. EXAMPLES
[0068] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to these examples.
[0069] Test 1 <Example 1> (Production of liquid crystal polymer powder) In Example 1, first, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 315° C.) were prepared as the LCP raw material. The LCP material was a copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid.
[0070] This LCP raw material was coarsely pulverized using a cutter mill (MF10 manufactured by IKA). The coarsely pulverized LCP was passed through a 3 mm diameter mesh provided at the outlet of the cutter mill to obtain coarsely pulverized LCP.
[0071] Next, the coarsely ground LCP was finely ground in a liquid nitrogen bead mill (Imex Corporation, LNM-08, vessel capacity: 0.8 L). Specifically, 500 mL of media and 30 g of the coarsely ground LCP were placed in a vessel and ground for 120 minutes at a rotation speed of 2000 rpm. The media used were zirconia (ZrO 2 ) beads were used. In the liquid nitrogen bead mill, the coarsely pulverized LCP is dispersed in liquid nitrogen and then wet-pulverized. In this way, the coarsely pulverized LCP was pulverized in the liquid nitrogen bead mill to obtain granular finely pulverized LCP.
[0072] The particle size of this finely ground LCP was measured. In the particle size measurement, the finely ground LCP dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then set in a particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.) using a laser diffraction scattering method, and the particle size was measured. As the dispersion medium, Ekinen (registered trademark, Japan Alcohol Sales Co., Ltd.), a mixed solvent mainly composed of ethanol, was used. The measured value of D50 of the finely ground LCP was 23 μm.
[0073] Next, the dispersion liquid obtained by dispersing the finely pulverized LCP in the equene was sieved through a mesh with an opening of 53 μm to remove the coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the mesh was collected. The yield of the finely pulverized LCP after removing the coarse particles was 85% by mass.
[0074] Next, the finely pulverized LCP from which the coarse particles had been removed was dispersed in a 20% by mass ethanol solution. The ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a nozzle diameter of 0.2 mm and a pressure of 200 MPa, to form fibers. As the wet high-pressure crushing device, a high-pressure disperser (Nanoveita manufactured by Yoshida Kikai Kogyo Co., Ltd.) was used. The ethanol slurry in which the finely pulverized LCP was dispersed was dried using a spray dryer to obtain an LCP powder. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 0.8 μm.
[0075] (Production of porous bodies) The LCP powder obtained above was dispersed in a 50% by mass aqueous ethanol solution, which was a dispersion medium, to form a slurry.
[0076] Next, the slurry-like LCP powder was placed on an 80-mesh wire netting made of polyester microfiber nonwoven fabric (basis weight: 14 g / m 2 The LCP fiber mat was made by papermaking using a square sheet machine (Kumagaya Riki Kogyo Co., Ltd.) on a sheet of paper with a weight of 35 g / m. 2 The amount of LCP powder was adjusted so that the LCP fiber mat was dried in a hot air dryer and peeled off from the polyester microfiber nonwoven fabric to form an LCP fiber mat.
[0077] Next, the LCP fiber mat was placed on a stainless steel tray and heated in a hot air inert oven (KOYO THERMO SYSTEMS CO., LTD., inert gas oven INH-21CD). Specifically, the LCP fiber mat was heated at 260° C. for 60 minutes under a nitrogen stream. As a result, a porous body was obtained.
[0078] <Examples 2 to 3, Comparative Example 1> In Examples 2 to 3 and Comparative Example 1, the heating temperatures in the hot air inert oven were 270° C., 280° C., and 250° C., respectively. Except for these, LCP powders were produced in the same manner as in Example 1, and porous bodies were obtained.
[0079] <Examples 4 to 6, Comparative Example 2> In Examples 4 to 6 and Comparative Example 2, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 340°C) were prepared as the LCP raw material. The LCP material was a copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid. Except for changing the LCP raw material to the above, LCP powder was produced in the same manner as in Example 1. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 0.9 μm.
[0080] In Examples 4 to 6 and Comparative Example 2, the heating temperatures in the hot air inert oven were 280° C., 290° C., 300° C., and 270° C., respectively. Other than that, porous bodies were obtained in the same manner as in Example 1.
[0081] <Example 7> In Example 7, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 430°C) were prepared as the LCP raw material. The LCP material was a copolymer of parahydroxybenzoic acid, terephthalic acid, and dihydroxyphenyl. Except for changing the LCP raw material to the above, an LCP powder was produced in the same manner as in Example 1. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 1.1 μm.
[0082] The LCP powder obtained above and an acrylic resin powder (average particle size: 2 μm) serving as a resin binder were weighed out so that the volume ratio was 1:1, and the mixture was dispersed in a 50% by mass ethanol aqueous solution serving as a dispersion medium to form a slurry. Next, the slurry-like resin mixture was treated in the same manner as in Example 1 to form a resin mixture mat.
[0083] The resin mixture mat obtained above was hot-pressed under conditions of 60°C and 0.6 MPa to produce a resin mixture film. The resin mixture film was then placed on a stainless steel tray and heated in a hot air inert oven similar to that of Example 1. Specifically, the heat treatment was performed at 380°C for 60 minutes under a nitrogen stream. This resulted in the porous body of Example 7.
[0084] <Example 8> In Example 8, a porous body was obtained in the same manner as in Example 7, except that the LCP powder and the acrylic resin powder were weighed out so that the volume ratio was 1:3.
[0085] <Reference example 1> Reference Example 1: A fabric with a basis weight of 4 g / m 2 A commercially available LCP meltblown nonwoven fabric was prepared.
[0086] [Observation of porous materials] 3 to 8 are photographs (SEM images) of the cross sections of the porous bodies in Examples 1 to 3 and 7, Comparative Example 1, and Reference Example 1. From the photographs in Figs. 3 to 8, it can be seen that the porous bodies in the Examples contain many fibers with a thicker fiber diameter than the porous bodies in the Comparative Examples, and the fibers are fused together. It can also be seen that the porous body in Comparative Example 1 contains many fibers with a thin fiber diameter, and the fibers are not fused together sufficiently. It can also be seen that Reference Example 1 is made of fibers that are significantly thicker than those in the Examples, and the shape of the pores is simpler than those in the Examples. In addition, when a porous body was obtained by heating at a temperature (over 280°C) higher than the heating temperature in the above-mentioned Examples, it was confirmed that many fibers with a thicker fiber diameter were contained and the fibers were fused together up to 310°C, that is, a temperature 5°C lower than the melting point of the LCP raw material, but it was confirmed that the fibers softened and the porous structure could not be maintained at a temperature above 310°C.
[0087] [Measurement of pore distribution] For each of the porous bodies according to Examples 1 to 8, Comparative Examples 1 and 2, and Reference Example 1, the pore distribution was measured using a mercury intrusion porosimeter (Autopore V9605, manufactured by Micrometrics). The results are shown in Table 1 as "average pore diameter (μm)," "cumulative pore volume (mL / g)," and "cumulative pore specific surface area (m 2 / g)" column.
[0088] [ISO air permeability measurement] The ISO air permeability was measured for each of the porous bodies according to Examples 1 to 8, Comparative Examples 1 to 2, and Reference Example 1 using a Gurley densometer (Gurley-type air permeability tester, manufactured by Yasuda Seiki Seisakusho Co., Ltd.). Air permeability is the average flow rate of air permeating per unit area, unit pressure difference, and unit time, and the higher the value, the easier the air permeates. The ISO air permeability was measured in accordance with JIS P8117:2009 "Paper and paperboard-Air permeability and air resistance test method (intermediate range)-Gurley method". The results are shown in the "ISO air permeability (μm / Pa·s)" column in Table 1. As described above, the higher the ISO air permeability value, the easier the air permeates, but as the value increases, the density of the porous body decreases and the strength may become insufficient. Therefore, in the present disclosure, 40 μm / Pa·s or less is considered to be good. Note that, for Reference Example 1, the value was measured by stacking nine LCP melt-blown nonwoven fabrics.
[0089] [Measurement of tensile strength] The tensile strength of the porous bodies according to each of Examples 1 to 8, Comparative Examples 1 and 2, and Reference Example 1 was measured using a dynamic viscoelasticity measuring device (RSA-G2, manufactured by TA-Instruments). Specifically, for the porous bodies, a test piece of 5 mm x 25 mm was used, and the body was elongated under conditions of a gripping distance of 13 mm and a pulling speed of 0.6 mm / min, and the load value at break was calculated by dividing it by the cross-sectional area excluding the pores. The results are shown in Figures 1 and 2 and Table 1 under "Tensile strength (N / mm 2 The number of test pieces for each test was 3, and the values in Table 1 are their average values.
[0090] [Table 1]
[0091] As shown in Figures 1-2 and Table 1, the porous bodies of Examples 1-8 have higher tensile strength than those of Comparative Examples 1-2. This is thought to be because, as can be seen from the SEM photographs of Figures 3-7, the thin fibers start to fuse at a temperature about 60°C lower than the melting point of the LCP powder (255°C in Examples 1-3 and Comparative Example 1, and 280°C in Examples 4-6 and Comparative Example 2), and the tensile strength improves as the amount of fusion between the fibers increases. In Reference Example 1, the average pore diameter is nearly 10 times larger, and the properties as a porous body, such as filtration properties, are significantly inferior.
[0092] It is also found that the porous bodies according to Examples 7 and 8 have an extremely fine average pore size of 1.0 μm or less. It is believed that such porous bodies having a fine average pore size have excellent strength and filtration characteristics.
[0093] Although not shown in Figures 1 and 2 and Table 1, when a porous body was obtained by heating at a temperature higher than the heating temperature in the above-mentioned examples, the tensile strength increased up to a temperature 20 to 30°C lower than the melting point of the LCP raw material, but no further increase in tensile strength was confirmed even when the temperature was increased to 5°C lower than the melting point of the LCP raw material. Furthermore, when the temperature exceeded 5°C lower than the melting point of the LCP raw material, waviness and large holes occurred, making it impossible to maintain the shape of the film, and therefore the tensile strength could not be measured.
[0094] Test 2 <Example 9> In Example 9, the same LCP powder as in Example 1 was used to form an LCP fiber mat through a coating process and a drying process.
[0095] First, the same LCP powder as in Example 1 was dispersed in butanediol, which was a dispersion medium, to form a paste.
[0096] Next, the paste-like LCP powder was applied to the roughened surface of a 200 mm square, 12 μm thick electrolytic copper foil (FWJ-WS-12, manufactured by Furukawa Electric Co., Ltd.) using a 160 mm square metal plate. The electrolytic copper foil to which the paste-like LCP powder was applied was heated to 180° C. on a hot plate to vaporize the butanediol dispersion medium, thereby drying the paste-like LCP powder on the electrolytic copper foil. In this way, a thin LCP fiber mat was formed on the electrolytic copper foil.
[0097] The above-mentioned paste-like LCP powder was further applied onto this thin LCP fiber mat. The applied paste-like LCP powder was dried in the same manner as the previously applied paste-like LCP powder was dried. In this way, the above-mentioned application and drying were repeated several times, and the basis weight was increased to 15 g / m2. 2 The LCP fiber mat was formed on an electrolytic copper foil.
[0098] The electrolytic copper foil on which the LCP fiber mat was formed was heated at 280° C. for 60 minutes under a nitrogen gas flow using a hot air inert oven similar to that used in Example 1. This resulted in a copper foil composite in which a porous body having a thickness of about 70 μm was formed on a part of one side of the copper foil.
[0099] <Example 10> In Example 10, PTFE (irregular shape, average particle size: 4.0 μm, melting point: 331° C.) was prepared as the additive.
[0100] PTFE and the same LCP powder as in Example 1 were dispersed in butanediol, a dispersion medium, to form a paste. The mixing ratio of PTFE and LCP powder was 5:5 by volume. A copper foil composite was obtained in which a porous body having a thickness of about 50 μm was formed on a part of one side of the copper foil by the same manufacturing process as in Example 9 except for the above.
[0101] <Example 11> In Example 11, boron nitride powder (flake-like, average particle size: 0.5 μm) was prepared as an additive.
[0102] Boron nitride powder and the same LCP powder as in Example 1 were dispersed in butanediol, a dispersion medium, to form a paste. The mixing ratio of the boron nitride powder and the LCP powder was 5:5 by volume. A copper foil composite was obtained in which a porous body with a thickness of about 50 μm was formed on a part of one side of the copper foil using the same manufacturing process as in Example 9, except for the above.
[0103] [Observation of copper foil composite] As described above, in the copper foil composites of Examples 9 to 11, the porous body could be formed not on the entire surface of the copper foil but on a part of the copper foil. Furthermore, even when the copper foil composites of Examples 9 to 11 were rolled, the porous body did not peel off from the copper foil, and no warping or undulation occurred.
[0104] [Water repellency test] A water repellency test was carried out for Examples 9 and 10. Specifically, pure water or ethanol aqueous solutions of various concentrations (50 mass%, 60 mass%, 70 mass%, and 80 mass%) were dropped onto the portion of each copper foil composite where the porous body was formed, and the presence or absence of adsorption was confirmed.
[0105] In Example 9, pure water was not adsorbed to the porous body when dropped, but it was confirmed that a 50% by mass ethanol aqueous solution was adsorbed to the porous body when dropped. Similarly, adsorption was confirmed in 60% by mass, 70% by mass, and 80% by mass ethanol aqueous solutions.
[0106] On the other hand, in Example 10, pure water was not adsorbed to the porous body when dropped, and neither was there any adsorption in 50 mass%, 60 mass%, or 70 mass% ethanol aqueous solutions. However, it was confirmed that an 80 mass% ethanol aqueous solution was adsorbed to the porous body when dropped.
[0107] These test results show that by mixing PTFE as an additive with LCP powder to form a porous body, it is possible to impart a high level of water repellency.
[0108] [Heat dissipation test] A heat dissipation test was carried out for Examples 9 and 11. Specifically, a copper plate was placed on a hot plate heated to 80° C., and each of the copper foil composites of Examples 9 and 11 was placed on top of the copper plate, and the surface temperature was measured by thermography.
[0109] The surface temperature of the copper foil composite of Example 11 was 5°C higher than the surface temperature of the copper foil composite of Example 9. These test results show that heat dissipation properties can be imparted by mixing boron nitride powder as an additive with LCP powder to form a porous body.
[0110] In addition, in this embodiment, a water repellency test and a heat dissipation test were carried out, but it is believed that the porous body can be provided with functions that are possessed by additives other than water repellency and heat dissipation.
[0111] In the above-described embodiment, configurations that can be combined may be combined with each other.
[0112] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.
Claims
1. A method for producing a porous body containing a liquid crystal polymer powder, comprising the steps of: A dispersing step of dispersing the liquid crystal polymer powder made of liquid crystal polymer fibers in a dispersion medium to obtain the liquid crystal polymer powder in a paste or slurry state; a matting step of drying the liquid crystal polymer powder in a paste or slurry form to form a liquid crystal polymer fiber mat; A heating step of heating the liquid crystal polymer fiber mat to obtain a porous body, The heating temperature in the heating step is in the range of −60° C. to −5° C. of the melting point of the liquid crystal polymer powder, The liquid crystal polymer powder contains fibrous particles made of a liquid crystal polymer, The average diameter of the fibrous particles made of the liquid crystal polymer is 2 μm or less, The porous body has an average pore size measured by mercury intrusion porosimetry of 10 μm or less, The method for producing a porous body, wherein the porous body has a tensile strength of 25 N / mm 2 or more.
2. The method for producing a porous body according to claim 1 , further comprising adding an additive to the liquid crystal polymer powder in the dispersing step.
3. The method for producing a porous body according to claim 2, wherein in the mat-forming step, the liquid crystal polymer powder in a slurry state or a mixture of the liquid crystal polymer powder in a slurry state and the additive is formed into the liquid crystal polymer fiber mat or the mixture mat by a papermaking method.
4. The method for producing a porous body according to claim 3 , wherein the matt-forming step includes a coating step of coating a substrate with the liquid crystal polymer powder or the mixture in a paste form.
5. A method for producing a porous body containing a liquid crystal polymer powder, comprising the steps of: a dispersing step of dispersing the liquid crystal polymer powder and the binder resin in a dispersion medium to obtain a resin mixture of the liquid crystal polymer powder and the binder resin in a paste or slurry state; a matting step of drying the paste or slurry-like resin mixture to form a resin mixture mat; a heat pressing step of obtaining a resin mixture film by heat pressing the resin mixture mat; A heating step of obtaining a porous body by heating and removing at least a portion of the binder resin contained in the resin mixture film, The heating temperature in the heating step is in the range of −60° C. to −5° C. of the melting point of the liquid crystal polymer powder, The liquid crystal polymer powder contains fibrous particles made of a liquid crystal polymer, The average diameter of the fibrous particles made of the liquid crystal polymer is 2 μm or less, The porous body has an average pore size measured by mercury intrusion porosimetry of 1.0 μm or less, The method for producing a porous body, wherein the porous body has a tensile strength of 25 N / mm 2 or more.
6. A porous body comprising a liquid crystal polymer powder, The liquid crystal polymer powder contains fibrous particles made of a liquid crystal polymer, The average diameter of the fibrous particles made of the liquid crystal polymer is 2 μm or less, having an average pore size measured by mercury intrusion porosimetry of 10 μm or less; A porous body having a tensile strength of 25 N / mm 2 or more.
7. The porous body described in claim 6, further containing an additive.
8. The porous body described in claim 7, wherein the additive is at least one selected from the group consisting of polytetrafluoroethylene and nitride powder.
9. A porous body described in any one of claims 6 to 8, having an average pore diameter measured by mercury porosimetry of 1.0 μm or less.
Citation Information
Patent Citations
Nonwoven fabric, its production and substrate for printed circuit board
JP1998325065A
Printed circuit board substrate and its production
JP1999255908A
Liquid crystal polyester fiber and production of liquid crystal polyester nonwoven fabric
JP2000119952A
Heat-resistant nonwoven fabric
JP2002061063A
Resin laminate plate for printed wiring board
JP2002064254A